2021
DOI: 10.1002/ccr3.4466
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopia with proboscis: A rare congenital anomaly

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(34 citation statements)
references
References 18 publications
(33 reference statements)
0
34
0
Order By: Relevance
“…Nevertheless, according to recent studies, there is a balanced sex ratio among fetuses identified prenatally during the gestational period ranging from 16 to 36 weeks suggesting that there is no significant disparity in the rate of fetal loss between males and females at this advanced stage of pregnancy 12 . The etiology of this condition is still unknown exactly 1,2,7,9 . Multiple heterogeneous risk factors are related.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, according to recent studies, there is a balanced sex ratio among fetuses identified prenatally during the gestational period ranging from 16 to 36 weeks suggesting that there is no significant disparity in the rate of fetal loss between males and females at this advanced stage of pregnancy 12 . The etiology of this condition is still unknown exactly 1,2,7,9 . Multiple heterogeneous risk factors are related.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of lobar HPE, children can survive for several years with neurological and mental challenges. Both alobar and semi‐lobar HPE have been associated with the worst prognosis 2 and are not compatible with life 2,4,7 . Generally, the result will either be a miscarriage or a stillborn, and even if babies are born alive, they only survive a few hours after birth 2,3,6,7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclopia can be diagnosed using ultrasonography while the fetus is growing inside the uterus. [8] . This congenital disorder occurs between the third and fourth weeks of pregnancy, and conducting medical ultrasound after this time can usually show obvious signs of cyclopia or other forms of holoprosencephaly.…”
Section: Discussionmentioning
confidence: 99%